Modeling Strategies of Ductile Masonry Infills for the Reduction of the Seismic Vulnerability of RC Frames - Milanesi, Riccardo R.; Hemmat, Mehdi; Morandi, Paolo; Totoev, Yuri; Rossi, Andrea; Magenes, Guido (Frontiers in Built Environment, 2020)
The threat to human lives and the economic losses due to high seismic vulnerability of non-engineered traditional masonry infills subjected to earthquakes have been highlighted by several post-seismic surveys and experimental and numerical investigations. In the past decades, researchers have proposed different techniques to mitigate problems related to the seismic vulnerability of traditional masonry infills; however, a viable practical and universally accepted solution has not been achieved yet. Among the possible innovative techniques, the one using ductile (or pliable) infills have shown promising results in recent experimental tests. These infills have provided, indeed, a reduced in-plane stiffness and a very high displacement capacity. The research units of the University of Pavia/EUCENTRE (Italy) and the University of Newcastle (Australia) have proposed two different systems for ductile masonry infill based on dividing the masonry panel into a number of segments interconnected through horizontal sliding joints. The ductile masonry infill proposed by the University of Pavia subdivides the masonry panel into four horizontal sub-panels using specially engineered sliding joints and presents a deformable mortar at the infill/structure interface; while the one conceived by the University of Newcastle is made of mortar-less specially shaped masonry units capable of sliding on all bed joints. The experiments conducted on the two novel systems have permitted the calibration of two numerical macro-models capable to replicate the overall in-plane seismic response of these ductile masonry infills. One approach is based on a spring model, as usually adopted for traditional masonry infill; the other calibrates the response of a semi-active damper model. The calibrated macro-model approaches have been adopted to demonstrate the enhanced behaviour and the reduction of the seismic vulnerability of r.c. framed structures with the employment of the ductile infills in comparison to structures with non-engineered masonry infills.